2018
DOI: 10.1515/raon-2018-0005
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases polymorphisms as baseline risk predictors in malignant pleural mesothelioma

Abstract: Patients and methods. The study included 236 patients and 161 healthy blood donors as the control group. Ten different polymorphisms in three MMP genes were genotyped using a fluorescence-based competitive allele-specific assay (KASPar): MMP2 rs243865, rs243849 and rs7201, MMP9 rs17576, rs17577, rs2250889 and rs20544, and MMP14 rs1042703, rs1042704 and rs743257. In statistical analyses continuous variables were described using median and range (25%-75%), while frequencies were used to describe categorical vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Matrix metalloproteinases are considered to be regulatory factors of tumour microenvironment and carcinogenesis (Strbac et al 2018). The MMPs are involved in the key ECM degradation of proteolytic enzyme family (Curran et al 2004;Chen KE et al 2018;Qiao et al 2018) and are used to disrupt the interaction of cells-cells and cells-ECM by tissue remodelling.…”
Section: Discussionmentioning
confidence: 99%
“…Matrix metalloproteinases are considered to be regulatory factors of tumour microenvironment and carcinogenesis (Strbac et al 2018). The MMPs are involved in the key ECM degradation of proteolytic enzyme family (Curran et al 2004;Chen KE et al 2018;Qiao et al 2018) and are used to disrupt the interaction of cells-cells and cells-ECM by tissue remodelling.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that apart from clinical characteristics such as C-reactive protein or tumor stage, serum and genetic markers may be associated with treatment outcome in MM [10,[18][19][20][21][22][23][24][25][26][27][28][29]. disease risk, diagnosis and treatment are also emerging [31]. Mesothelin is the only clinically validated biomarker in the diagnosis of mesothelioma.…”
Section: Biomarker Guided Chemotherapy Treatment In Malignant Mesothementioning
confidence: 99%
“… 20 On the other hand, MMP2 polymorphism was suggested to have a protective role in MM. 21 Furthermore, two of the investigated MMP9 single nucleotide polymorphisms (SNPs) had significant but opposing effect on time to progression (TTP) and overall survival (OS) in MM. 22 FASL-844 polymorphism could predict progression free survival (PFS) in MM patients receiving platinum based chemotherapy.…”
Section: Introductionmentioning
confidence: 99%